Platinum(ii) as an assembly point for carbide and nitride ligands. Issue 57 (27th June 2019) - Reinholdt, Anders; Bendix, Jesper
Abstract : The sequential treatment of (Cy3 P)2 Cl2 RuC with [PtCl2 (C2 H4 )]2 and (dbm)2 CrN affords a platinum(ii ) center coordinated by both carbide and nitride ligands. Abstract : The sequential treatment of (Cy3 P)2 Cl2 RuC with [PtCl2 (C2 H4 )]2 and (dbm)2 CrN affords trans -(Cy3 P)2 Cl2 RuC–PtCl2 –NCr(dbm)2, in which a platinum(ii ) center is coordinated by both carbide and nitride ligands. ESR spectroscopy indicates that the carbide–nitride complex is loosely associated and that its unpaired electron remains localized mainly at the chromium center.